Pengaruh Media Pembelajaran Teka-Teki Silang Terhadap Hasil Belajar Peserta Didik Kelas IV Sekolah Dasar - Lina Fauziyah; H. Dadang Iskandar; Abdul Mu’min Saud (Jurnal Pendidikan Indonesia (JOUPI), 2023)
This research is motivated by the existence of problems in the field regarding the low learning outcomes of students in conventional learning, lack of utilization of facilities, infrastructure, and learning media, especially crossword learning media. This study aims to determine the effect of crossword learning media on the learning outcomes of grade IV elementary school students. The method used in this research is a quantitative method of experimentation with a quasi experimental design type nonequivalent group design. Data was collected using observation, pretest and posttest techniques. By determining respondents as a sample of 20 students using purposive sampling type. The results showed that both the control class and the experimental class conducted learning in accordance with the stages of the learning media used. Because the two classes were given different treatments, the results obtained were different. There is a significant influence on student learning outcomes between learning using crossword puzzle learning media and conventional learning. This can be proven based on the acquisition of the Independent Sample T-test test results seen from Equal variances assumed at the Sig value. (2-tailed) which is 0.000 <0.005, it means that Ho is rejected and Ha is accepted. Through the effect size test, it can also be seen that there is a big influence in learning activities using crossword learning media on student learning outcomes of 4.09. With that, researchers can conclude that there is a significant effect of crossword learning media on the learning outcomes of fourth grade students of SDN Gekbrong 1 Cianjur Regency.